Anhydrous multi-hybrid absorbent with low viscosity and high regeneration efficiency for post-combustion CO2 capture. (15th January 2023) - Ding, Yudong; Ma, Lijiao; Yang, Xiaoqiang; Zhu, Xun; Wang, Hong; Cheng, Min; Liao, Qiang
Abstract: To reduce CO2 emissions, a new anhydrous multi-hybrid absorbent is developed for post-combustion CO2 capture. It was synthesized using tetraethylenepentamine-modified porous silica nanoparticles (TEPA-PSNs) as host unit and 2-[2-(dimethylamino)ethoxy]ethanol (DMEE) as solvent. The density and viscosity were higher with more TEPA-PSNs and lower temperatures. The viscosity of 50%-TEPA-PSNs/DMEE increased from 9.76 mPa s to 267.98 mPa s as TEPA-PSNs concentration rose from 5% to 20% at 27 °C. The effects of host unit concentration, amine group loading content, CO2 concentration in the gas phase, and temperature on CO2 absorption performance were investigated. The optimum absorption capacity was obtained with suitable TEPA-PSNs concentration and TEPA loading content to avoid the harmful effects of pore structure blockage and high viscosity on mass transfer. For 50%-TEPA-PSNs-10%/DMEE, higher CO2 concentration allowed better absorption capacity, which was 0.419 mmol/g at 20% CO2 . The influence of increasing temperature on absorption capacity was first promoted and then inhibited, which was 0.410 mmol/g at 57 °C. Under 80 °C and N2 atmosphere regeneration conditions, the absorption capacity reached 95.0% of the initial use after five cycles. The absence of water in TEPA-PSNs/DMEE diminishes energy consumption and degradation. It is a promising CO2 capture material with low viscosity for post-combustion CO2 capture. Highlights: Anhydrous absorbent exhibits a low viscosity and high regeneration efficiency. The variation patterns of absorbent density and viscosity are revealed. The absorption performance is studied for post-combustion CO2 capture.